Flexible, auxetic and strain-tunable two dimensional penta-X2C family as water splitting photocatalysts with high carrier mobility. Issue 13 (14th March 2019) - Sun, Songsong; Meng, Fanchen; Xu, Yuanfeng; He, Jian; Ni, Yuxiang; Wang, Hongyan
Abstract : Penta-X2 C (X = P, As and Sb): a novel two dimensional family for photo-catalytic water splitting. Abstract : Two dimensional materials have been regarded as promising candidates for photocatalytic water splitting. Herein, we systematically investigated the potential of a novel two dimensional penta-X2 C (X = P, As, Sb) family for photocatalytic water splitting by means of density functional theory. The penta-X2 C family consists of semiconductors with indirect band gaps of 2.64 eV, 2.09 eV and 1.35 eV for X = P, As and Sb, respectively. Notably, the band edge positions of penta-P2 C and penta-As2 C can perfectly satisfy the redox potentials of photocatalytic water splitting via strain engineering, whereas penta-Sb2 C only meets the reduction potential. The ultrahigh (up to 10 3 –10 5 cm 2 V −1 s −1 ) and anisotropic carrier mobilities are crucial to suppressing the photogenerated electron-hole pair recombination. Meanwhile, the penta-X2 C family exhibits excellent light absorption in the visible-ultraviolet region, favorable for the utilization of sunlight. In addition, compared with other common 2D materials such as graphene and h-BN, the penta-X2 C family possesses a relatively smaller Young's modulus and larger critical strain, while penta-X2 C have large negative Poisson's ratios of −0.103, −0.079 and −0.077, respectively. These results testify that the penta-X2 C family has potential applications not only in photocatalytic water splitting but also in designing 2D electromechanical and optoelectronic devices.